The Impact of Big Class Size on The Performance of English at U.C.E in Selected Secondary Schools of Shuuku Sub-County Sheema District. - Akankunda, Bronnet (Kabale University, 2024)
In 2006 the government of Uganda launched Universal Secondary Education (USE) this led to massive enrollment of students in Shuuku in Uganda at large Shuuku Sub-County, Sheema District in particular. As enrollment increased, physical facilities like classrooms, learning aids, and teachers were not increased and this caused continued deterioration of students' performance in classes. More so, different students from different backgrounds and behaviors were recruited. However private schools which have a minimum number of students per class have continued to perform well. It is against this background that the researcher intends to carry out a study to establish whether there is an impact of big Class Size and students' academic performance in English. Therefore, the purpose of this study was to assess the impact of Big Class Size on the Performance of English at U.C.E in Selected Secondary Schools of Shuuku Sub-County Sheema District.